Hustle : - Patel, Neil (Rodale, 2016)
A dynamic, game-changing guide to finding success and fearlessly outsmarting the system Too often we feel like underdogs fighting a system that stacks the odds against us. We work hard, follow the rules, and dream of a better life. But these days, working harder doesn't always lead to fulfillment. In fact, according to Gallup research, nearly 90 percent of people feel disconnected from their jobs. So how do you break free from the drudgery and achieve more success on your own terms? You hustle. The secret lies in making manageable tweaks and placing small bets on pursuits that propel you from who you are today to the person you're destined to become. In Hustle, Neil Patel, Patrick Vlaskovits, and Jonas Koffler -- three of the nation's top entrepreneurs and consultants -- have teamed up to teach you how to look at work and life through a new lens -- one based on discovering projects you enjoy and the people and opportunities that support your talents, growth, income, and happiness. The authors reveal their groundbreaking three-part framework of Heart, Head, and Habits. Along the way, you will learn to redefine hustle as the optimal path to success using powerful, often counterintuitive, advice, including: Why you must own your dreams, not rent dreams from others. Ways to create your own luck and "POP" How to betray yourself to stay true to yourself -- and develop your potential. The four major career hustles and the path that's best for you More than just an inspirational career guide, Hustle aims to fundamentally transform the way you work and live, and give yourself permission to thrive in today's uncertain world.